Spatial and temporal distribution of phytoplankton as indicator of eutrophication status in the Cienfuegos Bay, Cuba - Moreira,Angel (2014)
An important consequence of eutrophication is the increased prevalence of harmful algal blooms that affect transitional and coastal waters, and ecosystems in open seas. In this work, data on phytoplankton biomass, presence of harmful/toxic algal blooms and bottom dissolved oxygen were analyzed as indicators of overall eutrophic condition in the Cienfuegos Bay, Cuba. Samples were collected every three months during the year 2009 at fifteen representative stations within the bay. In the dry and early rainy seasons, high chlorophyll a values, harmful/toxic dinoflagellate blooms and fish mortality episodes were encountered within riverine-urban wastewater discharge zones, whilst most part of the bay did not evidence symptoms of eutrophication. During the rainy season, some stations showed biological stress-hypoxia for the bottom water oxygen, and a strong increase in spatial dispersion was observed in the phytoplankton biomass, due to a substantial increment in not toxic diatom abundance, resulting in a moderate level of eutrophic conditions for chlorophyll a in the entire bay. The key factor that supports the seasonal variation in phytoplankton composition and abundance appears to be the water residence time inside the bay.